Polystyrene/thermoplastic polyurethane interpenetrating network-based nanocomposite with high-speed, thermo-responsive shape memory behavior - Ghosh, Tuhin; Voit, Brigitte; Karak, Niranjan (Polymer, 2020)
In the recent years, generation of flexible, mechanically tough, shape memory (SM) polymers has gained a remarkable significance both in academic section and in the field of soft robotics, smart textiles, self-deployable structures (especially used in aerospace), actuators, bio-medical devices and so on. But designing of such materials poses a credible challenge to researchers in the field. Hence, in this work, we develop a bis(hydroxyalkyl)-poly(dimethylsiloxane) capped-(3-aminopropyl)trimethoxysilane functionalized-hydroxy iron oxide anchored-reduced graphene oxide nanohybrid which serves as a reinforcing agent for the generation of nanocomposites with SM, self-tightening and hydrophobic attributes. The prepared polystyrene/thermoplastic polyurethane (PS/TPU) interpenetrating network (IPN) nanocomposites recover their original shape at a faster rate (within 20–40s upon thermal heating and within 100–140s upon exposure to sunlight) compared to other similar type SM materials (require h to min). Moreover, the nanocomposites also showed thermally actuated artificial muscle-like and self-tightening behaviors. In addition, the nanocomposite containing 1 wt% nanohybrid demonstrated >200% increase in tensile strength, >120% increase in initial thermal degradation temperature, and strong surface hydrophobicity (static contact angle >120°). Therefore, the reported nanocomposites have considerable prospect for different smart applications.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Artificial muscle; Interpenetrating network; Polyurethane; Shape memory